Pemikiran Ekonomi Ibnu Taimiyah: Konsep Mekanisme Pasar, Harga Adil, dan Peran Pemerintah dalam Ekonomi - Farah Qalbia; M. Reza Saputra (Master Manajemen, 2023)
This research examines the economic thought of Ibn Taymiyyah, a prominent scholar from the 13th to early 14th century, focusing on his concepts of market mechanisms, just price, and the role of government in the economy. Using a qualitative method with a historical approach, this study analyzes Ibn Taymiyyah's works and related secondary literature. The results show that Ibn Taymiyyah had a deep understanding of market functions and price determination through the interaction of supply and demand. He viewed the market as a natural system to meet human needs but also recognized the necessity of government intervention in certain situations to ensure justice and social welfare. Ibn Taymiyyah also emphasized the importance of business ethics and fair competition while opposing monopolistic practices and hoarding of goods. Ibn Taymiyyah's economic thoughts are relevant not only in the historical context but also in providing moral and ethical guidance for contemporary economic practices.